2019
DOI: 10.3390/ijerph16071106
|View full text |Cite
|
Sign up to set email alerts
|

The Defining Role of Environmental Self-Identity among Consumption Values and Behavioral Intention to Consume Organic Food

Abstract: Consumption values and self-identity are the essential antecedents of consumer sustainable behavior. By integrating the theory of consumption values and self-identity approach, this research explores the relationship among consumption values (functional, social, conditional, epistemic and emotional), environmental self-identity and the behavioral intention to consume organic food. The data was collected from 406 organic food consumers through a structured questionnaire in Lahore (Pakistan). Using the PLS-SEM a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
92
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 110 publications
(116 citation statements)
references
References 84 publications
(133 reference statements)
22
92
0
2
Order By: Relevance
“…The results reveal that conditional value is positively associated with the consumer intention to consume organic food (β = 0.197, t = 4.932 > 1.64, p < 0.05). Previous research validate this result [2,4,6,23,66]. It means situations like discounts, promotions, incentives, easy availability of organic food can lead consumers towards organic food consumption.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…The results reveal that conditional value is positively associated with the consumer intention to consume organic food (β = 0.197, t = 4.932 > 1.64, p < 0.05). Previous research validate this result [2,4,6,23,66]. It means situations like discounts, promotions, incentives, easy availability of organic food can lead consumers towards organic food consumption.…”
Section: Discussionsupporting
confidence: 70%
“…Industrialization and economic growth have caused over-consumption, which creates many environmental problems (soil, air, water), deterioration of natural resources, depletion of the ozone layer and health hazards [2,3]. These negative impacts on the environment and ecological imbalances make consumers conscious about the consequences of their actions on the environment and human health [4]. In their search for the solution for these adverse effects, consumers are changing their food consumption patterns [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since 2013, organic and green products have gained popularity, and the increase in local organic produce sold has boosted consumer awareness and the use of green products. Regarding organic vegetables, two-thirds of Pakistani consumers residing in the Sindh province were aware of the concept, and the majority were willing to pay extra for these products (Akbar, Ali, Ahmad, Akbar, & Danish, 2019;Hasnain, 2018;Khan & Mohsin, 2017;Mangan, Shah, Laghari, Nangraj, & Nangraj, 2016;Qasim, Yan, Guo, Saeed, & Ashraf, 2019) Recruitment of study participants and description of samples An interception sampling technique was used. Potential study participants were approached as they patronized supermarkets, market squares, and greengrocery shops in city environments.…”
Section: Description Of Empirical Research Contexts: Organic Food Conmentioning
confidence: 99%
“…This is evident in the more significant effect of the opinions of others on organic food purchase intentions in Denmark than in Germany (Ruiz de Maya, L opez-L opez, & Munuera, 2011). Moreover, Qasim et al (2019) showed that the level of income does not influence Pakistani consumers' intention to consume organic food.…”
Section: Study Limitations and Future Research Suggestionsmentioning
confidence: 99%